PEMBERIAN BUAH BIT TPEMBERIAN BUAH BIT TERHADAP KENAIKAN KADAR HB IBU HAMILERHADAP KENAIKAN KADAR HB IBU HAMIL - Panca Nursela; Dwi Marlina Syukri; Devi Kurniasari; Yulistiana Evayanti; Nurul Isnaini (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
GIVING BEETROOT TO INCREASE LEVEL HB OF PREGNANT WOMEN Background anemia is a state of decreased levels of hemoglobin, hematocrine and the number of erythrocytes below normal values. Severe anemia if Hb <8 gr / dl, mild anemia if Hb> 8-11 gr / dl and normal in pregnant women Hb> 11 gr / dl. Based on the results of the survey conducted by researchers at UPTD Puskesmas Sudimoro Tanggamus Lampung in January-March 2019 there were 54 (100%) pregnant women who had anemia where 17 (31.4%) pregnant women had mild anemia. Purpose of this study is to know the effect of Beetroot juice on hemoglobin levels in pregnant women with anemia in UPTD Puskesmas Sudimoro Tanggamus Lampung.Methods is a pre-experimental action research with One group pretest - posttest design. There were 54 pregnant women with anemia who were anemic. Sample 17 people, the sampling technique used was purposive sampling. Data collection using observation sheets and data analysis used is the T-dependent test.Results of the study are known to be the average value of hemoglobin levels before administration of 9,835 beet juice and standard deviation of 0.5689. The average value of hemoglobin levels after giving beetroot juice is 11,771 and the standard deviation is 1.2164. Conclusion There Is The Effect Of Beetroot Juice On Increased Hemoglobin Levels In Pregnant Women With Anemia Pvalue = 0,000 <α = 0.005.Suggestions for pregnant women to consume beet juice regularly to prevent anemia and to consume foods that contain vitamin C. Keywords: anemia, beetroot, pregnant women ABSTRAK Latar Belakang anemia merupakan suatu keadaan adanya penurunan kadar hemoglobin, hematokrin dan jumlah eritrosit dibawah nilai normal. Anemia berat bila Hb < 8 gr/dl, anemia ringan jika Hb > 8-11 gr/dl dan normal pada ibu hamil Hb > 11 gr/dl. Berdasarkan hasil prasurvey yang telah peneliti lakukan di UPTD Puskesmas Sudimoro Tanggamus Lampung pada bulan Januari-Maret tahun 2019 terdapat 54 (100%) ibu hamil yang mengalami anemia dimana 17 (31,4%) ibu hamil mengalami anemia ringan.Tujuan diketahui Pengaruh Pemberian Jus Buah Bit Terhadap Kadar Hemoglobin Ibu Hamil Dengan Anemia Di UPTD Puskesmas Sudimoro Tanggamus Lampung.Metode tindakan pra eksperimen dengan rancangan One group pretest – posttest design. Seluruh ibu hamil yang anemia di terdapat 54 ibu hamil yang mengalami anemia. Sampel 17 orang, Teknik sampling yang digunakan purposive sampling. Pengumpulan data dengan menggunakan lembar observasi dan analisa data yang digunakan adalah uji T-dependent.Hasil penelitian diketahui Nilai rata-rata kadar hemoglobin sebelum pemberian Jus buah Bit 9.835 dan standar deviasi 0.5689. Nilai rata-rata kadar hemoglobin sesudah pemberian Jus buah Bit 11.771 dan standar deviasi 1.2164.Kesimpulan ada Pengaruh pemberian Jus buah Bit Terhadap peningkatan Kadar Hemoglobin Pada Ibu Hamil dengan anemia pvalue = 0,000 < α = 0,005.Saran bagi ibu hamil dapat mengkonsumsi jus buah bit secara rutin guna pencegahan terjadinya anemia serta mengkonsumsi makanan yang mengandung vitamin C. Kata Kunci: anemia, buah bit, ibu hamil